Implementasi Kebijakan Perparkiran Kota Depok dalam Meningkatkan Kesadaran Hukum Masyarakat terhadap Praktik Parkir Liar - Hudzaifah Nazhif Rabbani; Dadang Sundawa; Dwi Iman Muthaqin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the implementation of parking policy in Depok City in enhancing public legal awareness toward illegal parking practices. The research focuses on the implementation of Depok Mayor Regulation Number 16 of 2020 concerning the Licensing Procedures for Parking Facilities and Parking Fee Regulations. This study employs a qualitative approach using a case study method. Data were collected through in-depth interviews, field observations, and document analysis involving local government officials, parking managers, parking attendants, and parking service users. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the parking policy in Depok City has not been fully effective. The main weaknesses lie in limited policy socialization, inadequate supervision, and inconsistent law enforcement. These conditions contribute to low public legal awareness and the persistence of illegal parking practices in public spaces. Illegal parking practices negatively affect social order, public comfort, and the function of public spaces. This study concludes that the effectiveness of parking policy depends not only on regulatory frameworks but also on the quality of implementation and the internalization of legal awareness among the community.